PJOK Learning Strategies and Media During the Pandemic Period at SD Negeri 82 Bengkulu City - Marco Herwanto; Feby Elra Perdima; Martiani Martiani (Penerbit Jurnal Indonesia, 2023)
This study aims to: (1) find out the implementation of PJOK learning strategies and media during the pandemic at SD Negeri 82 Bengkulu City, (2) find out the teacher's efforts in improving PJOK learning strategies and media during the pandemic at SD Negeri 82 Bengkulu City, (3 ) Knowing the obstacles faced by PJOK teachers, students and parents of students in learning Physical Education at SD Negeri 82 Bengkulu City. This research is a qualitative descriptive research, data collection techniques using the methods of observation, interviews, and documentation. In this study, the subjects/informants were one PJOK subject teacher, three parents of students, and five grade IV B students at SD Negeri 82 Bengkulu City. The data analysis technique used is data reduction, data presentation, conclusion drawing and verification. The results of this study are online learning strategies and media in PJOK subjects at SD Negeri 82 Bengkulu City including the implementation of PJOK learning strategies and media during the pandemic, including; preliminary activities, core activities, and closing activities. Teachers' efforts in improving PJOK learning strategies and media during the pandemic, namely; familiarize students with reading books, increase students' motivation and enthusiasm for learning. And the obstacles faced by teachers, students, and parents in PJOK learning during the pandemic include; difficulties in making lesson plans, limited learning media, lack of knowledge and understanding of students' parents about IT.